Synthesis of Typical Isocopalane Diterpenes: ent-Spongian-16-one, ent-Isoagatholactone, and Anisodorin 5 - Ren, Jiangmeng; Zhao, Pu; Xiao, Xiong; Chen, Tianqi; Zeng, Bu-Bing (Synthesis, 2016)
A synthetic approach to the isocopalane diterpenes ent-spongian-16-one, ent-isoagatholactone, and anisodorin 5 is presented. ent-Spongian-16-one was prepared by using a tricyclic diterpene building block as the starting material. Furthermore, ent-spongian-16-one was easily converted into ent-isoagatholactone and anisodorin 5 through organic transformations.
Keywords: terpenoids; total synthesis; anisodorin 5; spongianone; isoagatholactone